Youtube Based Authentic English Content In Teaching Speaking A Qualitative Study At Zainul Hasan Genggong Islamic University - Dhini Sukma Aprilia; Muhammad Hifdil Islam; Zainuddin Zainuddin (Journal of English Language and Education, 2026)
This study emphasizes how crucial speaking abilities are to EFL instruction, especially when it comes to helping students become more proficient communicators in everyday situations. But there is still a disconnect between theoretical methods like Communicative Language Teaching and their actual use, particularly when it comes to using real digital media. The purpose of this project is to investigate how authentic English content from YouTube can be used to teach speaking and to analyze students' reactions. Through observations, interviews, and documentation, a qualitative approach was used. Although there are some drawbacks such a lack of engagement and technical difficulties, the results show that YouTube improves students' motivation, vocabulary, pronunciation, and confidence. The conclusion is that YouTube works well when paired with interactive exercises and suitable teaching techniques.